Analisis Service Quality Terhadap Kepuasan Konsumen Menggunakan Metode Customer Satisfaction Index (CSI) Dan Importance-Performance Analysis (IPA) Pada Aplikasi Mobile Banking Bank Syariah Indonesia (BSI) - Siti Mahmudah; Senia Kristanti; Hafsyahda Gustiani; Riski Septianingrum; Michell Aryasheila Amanda Putri; Murtiningsih Murtiningsih (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The more advanced digital technology, the more sophisticated the features provided by digital technology developers. The benefits of a sophisticated technology will support the development of a business, one of which is in the banking sector. This research is used to measure the level of satisfaction of BSI application users with the CSI and IPA methods to identify consumer performance and interests. This type of research is quantitative research. The sample used in this study amounted to 100 respondents with the sampling area sampling technique. Collecting data from questionnaires using a Likert scale. The results of the CSI test produce a satisfaction level of 0.8259, which means that the customer is very satisfied and the IPA method in quadrant 1, namely K9 (provides promised standards and quality) and K5 (product information is found easily) must improve its performance. Then, in quadrant IV, namely K12 (operational availability equals predicted availability until operational is available) and K17 (responsiveness in helping customer difficulties) their performance must be maintained. This research can be used as material for consideration in BSI bank in improving and increasing the quality of service that will be required.